ETHNOSCIENCE APPROACH TO MEASURE CREATIVE THINKING SKILLS PROFILE - Ahmad Khoiri (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
The urgency of research on creative thinking skills as a 21st century skill requirement for low-category high school students. The aim of the research is to determine the profile of creative thinking skills using an ethnoscience approach. The quasi-experimental method used 3 high schools with different cultural backgrounds (SMA A: City category, SMA B: Middle category, SMA C: Village category). Data collection of the Torrance Creative Thinking Test (TTCT) of 10 essay questions. Descriptive analysis techniques to determine the process of science reconstruction and the profile of creative thinking skills. The results showed that there were differences in the reconstruction and profile of students in the middle category of SMA B, the highest compared to SMA A (City) and SMA C (Village). Differences in cultural background greatly affect efforts to understand science through meaningful learning resources of ethnoscience. This approach has the opportunity and perspective of students in understanding scientific issues that are developing in society.